Decision Support Tools and Modeling Tools Report - Ministry of Water Resources and Meteorology, Cambodia; Supreme National Economic Council, Cambodia; Tonle Sap Authority; Hatfield Consultants; Culture and Environment Preservation Association (2013)
This report presents various decision support tools (DSTs) and modeling techniques for facilitating decision-making around water resource management. The objective here is to assess currently available and relevant DSTs, and to highlight the method of selecting most appropriate tool.